Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Treponema denticola / Prevotella intermedia Co-Infection Are Associated with Severe Periodontitis in a Thai Population - Torrungruang, Kitti; Jitpakdeebordin, Supawadee; Charatkulangkun, Orawan; Gleebbua, Yingampa (PloS one, 2015)
Periodontitis is a polymicrobial infection of tooth-supporting tissues. This cross-sectional study aimed to examine the associations between five target species and severe periodontitis in a Thai population. Using the CDC/AAP case definition, individuals diagnosed with no/mild and severe periodontitis were included. Quantitative analyses of Aggregatibacter actinomycetemcomitans (Aa), Porphyromonas gingivalis (Pg), Tannerella forsythia (Tf), Treponema denticola (Td), and Prevotella intermedia (Pi) in subgingival plaque were performed using real-time polymerase chain reaction. The association between target species and severe periodontitis was examined using logistic regression analysis. The study subjects comprised 479 individuals with no/mild periodontitis and 883 with severe periodontitis. Bacterial prevalence and quantity were higher in subjects with severe periodontitis than in those with no/mild disease. In the fully adjusted model, all species except Tf showed a dose-dependent relationship with periodontitis. The mere presence of Pg, even in low amount, was significantly associated with severe periodontitis, while the amount of Aa, Td, and Pi had to reach the critical thresholds to be significantly associated with disease. Compared to individuals with low levels of both Td and Pi, high colonization by either Td or Pi alone significantly increased the odds of having severe periodontitis by 2.5 (95%CI 1.7-3.5) folds. The odds ratio was further increased to 14.8 (95%CI 9.2-23.8) in individuals who were highly colonized by both species. Moreover, the presence of Pg and high colonization by Aa were independently associated with severe periodontitis with odds ratios of 5.6 (95%CI 3.4-9.1) and 2.2 (95%CI 1.5-3.3), respectively. Our findings suggest that the presence of Pg and high colonization by Aa, Td, and Pi play an important role in severe periodontitis in this study population. We also demonstrate for the first time that individuals co-infected with Td and Pi were more likely to have periodontitis than were those infected with a single pathogen.